2016
DOI: 10.17306/j.afs.2016.2.21
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a low-calorie diet or an isocaloric diet combined with metformin on sex hormones In obese women of child-bearing age

Abstract: Background. The infl uence of weight loss treatment on sex hormones profi le has been studied mainly in women with polycystic ovary syndrome (PCOS), but in obese premenopausal women without PCOS it still remains unclear. The aim of the study was to evaluate the eff ect of two approaches to obesity treatment on the serum level of sex hormones in obese women of child-bearing age without PCOS. Material and methods. 77 obese Caucasian women (aged 31.2 ±8.3 years) were randomized into two groups: 39 women received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…There were no significant differences in visceral fat reduction between the groups after equivalent weight loss. The significant reduction in VAT in the CRD group was consistent with previous studies’ results that have shown that weight reduction induced by CRD was associated with a significant improvement in WC and reduced fat mass [ 30 , 31 ]. However, after the same degree of weight loss, dulaglutide may have no additional benefits on VAT as compared with the effect resulting from diet intervention, suggesting that the extent of weight reduction, other than the type of intervention, explained most of the favorable effects of reducing visceral fat in overweight or obese individuals with PCOS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There were no significant differences in visceral fat reduction between the groups after equivalent weight loss. The significant reduction in VAT in the CRD group was consistent with previous studies’ results that have shown that weight reduction induced by CRD was associated with a significant improvement in WC and reduced fat mass [ 30 , 31 ]. However, after the same degree of weight loss, dulaglutide may have no additional benefits on VAT as compared with the effect resulting from diet intervention, suggesting that the extent of weight reduction, other than the type of intervention, explained most of the favorable effects of reducing visceral fat in overweight or obese individuals with PCOS.…”
Section: Discussionsupporting
confidence: 91%
“…Other research involving different populations have found similar results. Swora-Cwynar et al reported that reductions in body weight, WC, and body fat content were comparable between 12-week low-calorie diet and isocaloric diet plus metformin groups in premenopausal obese women [ 30 ]. Schübel et al reported no significant differences in body weight and VAT volume between intermittent calorie restriction and continuous calorie restriction in overweight or obese women [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 38 unique studies, investigators examined the effects of lifestyle interventions in 16 studies [ 12 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], bariatric surgery in 16 studies [ 35 , 36 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], and pharmacotherapy in 8 studies [ 67 , 68 , 69 , 70 , 71 ] ( Table 1 ). Two studies [ 35 , 36 ] that evaluated both lifestyle and bariatric surgery were counted within each of those respective intervention groupings.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 29 eligible studies reporting weight changes (11 lifestyle [ 12 , 38 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 48 , 49 ], 10 bariatric surgery [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 63 ], 8 pharmacotherapy [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]), the overall average weight loss was 13.8% (adj. avg.…”
Section: Resultsmentioning
confidence: 99%
“…Weight loss with lifestyle and dietary changes is the mainstay of management of women with PCOS, and it is associated with significant improvements in hyperandrogenaemia, menstrual irregularities, ovulation, and emotional wellbeing in this population [ 3 ]. Several dietary interventions have been proposed for the management of PCOS, including VLCDs [ 18 , 19 , 27 ], energy deficit diets [ 28 , 29 ], and low-GI [ 30 ] and ketogenic diets [ 31 , 32 ]. There is, however, no consensus on dietary interventions for optimal weight loss strategies [ 33 ].…”
Section: Discussionmentioning
confidence: 99%